Membrane-mediated control of hepatic JJ-hydroxy-fJ-methylglutarylcoenzyme A reductase - Sipat, Abdullah; Sabine, John R. (Portland Press, 1981)
Previously we [Sabine & James (1976) life Sci. 18, 1185-11921 proposed that the activity of hepatic β -hydroxy- β ·methylglutaryl-coenzyme A reductase is critically regulated by the fluidity of its supporting microsomal membrane'. In the present work we examined further this concept of membrane mediated control, with respect to the specific hypothesis that such control might Junction as a common mechanism both for the co-ordinated regulation of other enzymes affected by cholesterol feeding and also for the subcellular integration of the several physiological factors known to influence this enzyme's activity. Contrary to earlier expectations, this hypothesis now appears not to hold. We report here that, under those conditions of short-term cholesterol feeding that affected the reductase, a variety of other microsomal enzymes did not display membrane-function interactions, i.e. neither enzymes involved in cholesterol metabolism and also affected by cholesterol feeding (cholesterol 7α·hydroxylase), nor those involved in cholesterol metabolism and not affected by cholesterol feeding (hydroxymethylglutaryl-Co A hydrolase, acyl-CoA: cholesterol acyltransfernse). nor those not directly involved in cholesterol metabolism at all (glucose 6-phosohatase). Furthermore, we oberved no evidence for the operation of membrane-mediated control of the reductase in other situations known to influence its activity, i.e. starvation, diurnal rhythm, the very early stages of cholesterol feeding and various manipulations in vitro,